2019
DOI: 10.1021/acs.est.9b03565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Desalination Discharge on the Abundance and Diversity of Reef Fishes

Abstract: Global growth in desalination industries has increased the need for an evidence-based understanding of associated environmental impacts. We completed a seven-year assessment of the responses of fish assemblages to hypersaline discharge from the large Sydney Desalination Plant. At 12 times before, eight times during, and four times following the cessation of discharging hypersaline brine, we sampled reef fishes at two outlet sites and two close reference sites, as well as four reference sites that were located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…A potential explanation for the lack of recorded impacts may be high natural variability, which is typical of such seabed systems in combination with the rapid dilution undergone by the hypersaline brine after exiting the discharge pipe. An interesting aspect is the concentration of fish at the brine outfalls of the plants surveyed here, which is reminiscent of observations from Australia [48] and hitherto unreported for the Mediterranean. Even though only qualitative photographic surveys were conducted, they reveal the main fauna species found close to the brine discharge area and suggest overall increased fish density.…”
Section: Marine Environmental Impact Of Desalination Plantssupporting
confidence: 63%
See 1 more Smart Citation
“…A potential explanation for the lack of recorded impacts may be high natural variability, which is typical of such seabed systems in combination with the rapid dilution undergone by the hypersaline brine after exiting the discharge pipe. An interesting aspect is the concentration of fish at the brine outfalls of the plants surveyed here, which is reminiscent of observations from Australia [48] and hitherto unreported for the Mediterranean. Even though only qualitative photographic surveys were conducted, they reveal the main fauna species found close to the brine discharge area and suggest overall increased fish density.…”
Section: Marine Environmental Impact Of Desalination Plantssupporting
confidence: 63%
“…Overall, there is still a shortage of studies concerning Mediterranean marine life. Elsewhere in the world, for example, in the Red Sea, such a study has investigated brine impacts on the coral Fungia granulosa [70], whereas near Sydney, Australian scientists interestingly observed a strong increase in the abundance of fish around the outlet, which included substantially greater abundances of demersal and pelagic fish, as well as fishes targeted by recreational and commercial fishing near the recently-inaugurated desalination plant [48]. Further research should address the spatial scale of impacts, and also the underlying phy sicochemical drivers for the effects observed.…”
Section: Marine Environmental Impact Of Desalination Plantsmentioning
confidence: 99%
“…We cannot determine whether the effluent attracts some fish species or whether there is higher habitat diversity in the discharge area because we have no similar data from before the plant began operating. However, Kelaher et al (2020) recently reported an increase in local fish abundance and species richness related with the BD of a SWRO plant in Australia. In the present study, we also identified a decrease in fish abundance in both study areas from 2012 that could not be attributed to the discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusers represent the most environmentally friendly option for brine disposal. They have been shown to have minimal impacts on local fish populations [49], and have been employed with success at other plants in sensitive ecological environments such as the Sydney Desalination Plant in Sydney, Australia [50].…”
Section: Outfallmentioning
confidence: 99%